Young Men, Help-Seeking, and Mental Health Services: Exploring Barriers and Solutions. Issue 1 (January 2018) - Lynch, Louise; Long, Maggie; Moorhead, Anne
International research has identified young men as reluctant to seek help for mental health problems. This research explored barriers and solutions to professional help seeking for mental health problems among young men living in the North West of Ireland. A qualitative approach, using two focus groups with six participants each and five face-to-face interviews, was conducted with men aged 18 to 24 years (total N = 17). Data were analyzed using thematic analysis. Seven key themes of barriers to professional help seeking were identified: "acceptance from peers, " "personal challenges, " "cultural and environmental influences, " "self-medicating with alcohol, " "perspectives around seeking professional help, " "fear of homophobic responses, " and "traditional masculine ideals." Five key themes of solutions to these barriers included "tailored mental health advertising, " "integrating mental health into formal education, " "education through semiformal support services, " "accessible mental health care, " and "making new meaning." Interesting findings on barriers include fear of psychiatric medication, fear of homophobic responses from professionals, the legacy of Catholic attitudes, and the genuine need for care. This study offers an in-depth exploration of how young men experience barriers and uniquely offers solutions identified by participants themselves. Youth work settings were identified as a resource for engaging young men in mental health work. Young men can be encouraged to seek help if services and professionals actively address barriers, combining advertising, services, and education, with particular attention and respect to how and when young men seek help and with whom they want to share their problems.